Hemodynamic studies of platelet thrombosis using microfluidics. (4th July 2017) - Hastings, Susan M.; Griffin, Michael T.; Ku, David N.
Abstract: Platelets contribute to thrombus formation in a variety of ways. Platelet adhesion, activation, and thrombus growth depend greatly on the type of hemodynamic environment surrounding an inciting event. Microfluidic systems may be used to explore these relationships. In this review, we describe some important considerations required in the design of a microfluidic system and identify some limitations that may require use of a macroscale system.